Implementation of Good corporate Governance Principle in the Management and Accountability of Village-Owned Enterprises - Ambarwati, Dewi; lailawati, Fadillah Dwi; Assiddiq, Dafis Ubaidillah (Jurnal Cakrawala Hukum, 2023)
The Legal basis of BUM Desa as a legal entity has been stipulated in the laws and regulations in Indonesia, but in its implementation there are still problems that require professional management and accountability and apply the principles of good corporate governance so that BUM Desa can play a role in accordance with the mandate of the Village Law. This study aims to determine how BUM Desa Armada manages and is accountable for the management of BUM Desa in accordance with the general principles of good corporate governance and is analyzed legally. The results of the study indicate that BUM Desa Armada still requires strategic and inclusive arrangements regarding strengthening human resources, management of BUM Desa, selection of types, and business units to accountability in the field of business results. The suggestion that the researcher wants to give to BUM Desa ARMADA is to strengthen the synergy between BUM Desa implementing organizations and form an internal risk management committee so that it can minimize the potential for business losses. How to cite item: Madjid, Abdul. Ambarwati, Dewi, Fadilla Dwi Lailawati, and Dafis Ubaidillah Assidiq. â€œImplementation of Good corporate Governance Principle in the Management and Accountability of Village-Owned Enterprises.â€ Jurnal Cakrawala Hukum 14 no. 3 (2023): 235-253. DOI: 10.26905/idjch.v14i3.12368.